Uji Pasar terhadap Buah Pimento di Bali (Studi Kasus di Wilayah Badung dan Denpasar) - A, Wahyu Dwi; S, Ketut Budi; Budiasa, IW (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2017)
ABSTRACT Market Test on Pimento Fruits at Bali (Case Study in Badung and Denpasar Region) Pimento is one of potencial agriculture comodity will be developed. Pimento is one of a plant in category of chilli genus and its category of sweet chilli. Present Pimento are many consumed by at the high class consumer and foreign, and its selling just only at certaint supermarket. Paprika is easier got and many sell at market. This study aims to find out whether the pimento fruits able to compete with Paprika which has been exist in the market, to know whether Pimento fruits able to accept or not by the public in the market, to know what indicators become consumer considerations to buy and to consume Pimento. This study was conducted in Badung region especially Kuta area and conducted at supermarket that sell Pimento. Sample of consumer are 31 persons who was taken. Data analysis in was conducted by descriptive analysis and Mann Whitney test. The result shows Pimento fruits is not yet able to compete with Paprika fruits. Pimento price is Rp144.935,48/ kg, four times more expensive than Paprika that only Rp 35.854,83/kg. Mean of Paprika sales was 2,29 kg/person/month than Pimento was only 0,63 kg/person/month and mean of frequency the Paprika purchased by people 9,74 times/month more than Pimento that was only 3,19 times/month. Present Pimento acceptance is limited at middle class and foriegn and just only sell at certain place. Indicator become consumer consideration to buy Pimento as follows forms, aroma, colour, taste, and benefit as main course. We recommended that Pimento fruits need for wider production and promotion, marketing place, more marketed segmentation and cheaper price. Keywords: market test, Pimento, Paprika